THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON PURCHASING DECISIONS WITH CONSUMER TRUST AS AN INTERVENING VARIABLE ON XIAOMI SMARTPHONES (Case Study at Mi Shop Tebing Tinggi City) - Benhart Nainggolan; Suwadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study aims to analyze "The Effect Of Brand Image and Product Quality on Purchase Decisions With Consumer Trust As An Intervening Variable on Xiaomi Smartphones (Case Study on Mis Shop Tebing Tinggi City)". Quantitative method with a sample of 60 which is determined by the Slovin formula which is a Mi Shop Tebing Tinggi City Consumer. Based on the results of the analysis of hypothesis 1, it can be concluded that the first hypothesis is accepted, meaning that the Brand Image (X1) has an effect on the Consumer Trust variable (Z). Based on the results of the analysis of hypothesis 2, it can be concluded that the second hypothesis is rejected, meaning that the Product Quality variable (X2) has no effect on the Consumer Trust variable (Z). Based on the results of the analysis of hypothesis 3, it can be concluded that the third hypothesis is accepted, meaning that the Brand Image variable (X1) has an effect on the Purchase Decisions variable (Y). Based on the results of the analysis of hypothesis 4, it can be concluded that the fourth hypothesis is rejected, meaning that the Product Quality variable (X2) has no effect on the Puchase Decisions variable (Y). Based on the results of the analysis of hypothesis 5, it can be concluded that the fifth hypothesis is accepted, meaning that the Consumer Trust variable (Z) has an effect on the Purchase Decisions variable (Y). Based on the results of the analysis of hypothesis 6, it is accepted, meaning that the variable Consumer Trust (Z) can mediate the influence of the Brand Image (X1) on Purchase Decisions (Y). Based on the results of the analysis of hypothesis 7, it is accepted, meaning that the variable Consumer Trust (Z) can mediate the influence of the Product Quality (X2) on Purchase Decisions (Y).